Phenotyping 172 strawberry genotypes for water soaking reveals a close relationship with skin water permeance. - Hurtado, Grecia; Olbricht, Klaus; Mercado-Carmona, José Ángel; Posé-Albacete, Sara; Moritz, Knoche (PeerJ, 2024)
Water soaking is a commercially important disorder of field-grown strawberries that is exacerbated by surface wetness and high humidity. The objective was to establish the effect of genotype on susceptibility to water soaking. Three greenhouse-grown model ‘collections’ were used comprising a total of 172 different genotypes. Potential relationships between water soaking and water uptake characteristics, depth of the achene depressions, fruit firmness, cuticle mass and strain relaxation and microcracking were investigated. Further, the effect of downregulating the polygalacturonase genes (FaPG1 and FaPG2) on the susceptibility to water soaking was investigated. The collection of wild species was most susceptible to water soaking. Susceptibility to water soaking was strongly correlated with water uptake rate (mass of water, per fruit, per time). For the pooled dataset of 172 genotypes, 46% of the variability in water soaking was accounted for by the permeance of the skin to osmotic water uptake. Susceptibility to water soaking was not, or was only poorly correlated with measurements of fruit surface area or of the osmotic potential of the expressed fruit juice. The only exceptions were the wild Fragaria species which were highly variable in fruit size and also in fruit osmotic potential. For genotypes from the F2 and the wild species collections, firmer fruit were less susceptible to water soaking than softer fruit. There were no relationships between fruit firmness and susceptibility to water soaking in transgenic plants in which FaPG1 and FaPG2 were down-regulated. Susceptibility to water soaking was not related to cuticle mass per unit fruit surface area, nor to strain relaxation of the cuticle upon isolation, nor to achene position. In summary, strawberry’s susceptibility to water soaking has a significant genetic component and is closely and consistently related to the skin’s permeance to osmotic water uptake.
Keywords: Fenotipo; Fresas; Permeabilidad; Strawberry; Phenotyping; Water soaking; Water permeance